The renoprotective effects of sulodexide - Olde Engberink RH; Vogt L (Dove Medical Press, 2016)
Rik HG Olde Engberink, Liffert Vogt Department of Internal Medicine, Section of Nephrology, Academic Medical Center, University of Amsterdam, Amsterdam, the NetherlandsIn their meta-analysis, Li et al1 reported a renoprotective benefit of sulodexide in patients with diabetic nephropathy. This was the first meta-analysis to evaluate the potential anti-albuminuric effects of sulodexide in such patients. Albuminuria reduction with renin–angiotensin–aldosterone system inhibitors is known to beneficially affect renal outcome and represents, together with blood pressure control, the cornerstone of diabetic nephropathy treatment.2–6 As (residual) albuminuria is closely related with renal outcome and the reduction in albuminuria is linearly correlated with renoprotection, we need additional measures to reduce the burden of diabetic nephropathy.7 The meta-analysis of Li et al1 therefore addresses a very relevant topic.View original paper by Li and colleagues.